(untitled) (Research, Society and Development, 2022)
COVID-19 can trigger damage to the function and integrity of multiple cells, tissue or organs. In the progression of clinical manifestations, laboratory biomarkers can be used as predictors of prognosis to support in clinical conduction. This study aims to evidence an updated review of the literature of changes in biochemical and hematological laboratory tests of individuals with COVID-19 from articles prospected from the SciELO, LILACS and PubMed databases. Although in severe clinical spectrums, especially in patients admitted to intensive care unit, tissue lesions are more intense and more evident laboratory changes, can be observed in general in patients infected with SARS-CoV-2 increased levels of transaminases, alkaline phosphatase, gamma glutamyl transferase, bilirubin, urea, creatinine, lactic dehydrogenases, amylase, lipase, troponins, NT-ProBNP, pro-BNP, as well as reduction of MCV and MCHC, lymphopenia, neutrophilia, eosinopenia, thrombocytopenia, and prolongation of PT and aPTT.